RAPID PROTOCOL OF Aloe vera In Vitro propagation - & et al., Danial (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The current research was carried out to enhance Aloe vera propagation via tissue culture technique. BA at 0, 1, 2, 3, and 4 mg/l alone or combined with 0.1 mg/l NAA were used for shoot proliferation. The best result was recorded by using 2mgl-1 BAP (5.33 shoots/ explant). Meanwhile, combination between 2 mg/l BAP with (0.2, 0.4 and 0.6) mg/l kinetin, NAA or IBA were tested and best protocol was shown by using 2 mg1-1 BAP + 0.6 NAA which recorded 4.89 shoots/ explant. For rooting, MS medium at half and full strength salts were used supplemented with 0, 1, 2, 3, 4mgl-1 of NAA. The result revealed that 3 mg1-1 NAA at half strength of MS medium regenerate developed roots (8.67 roots / shoot) within 4 weeks. The well successful healthy plantlets were transferred into a potting mix composed of sand and peat moss which shows 100% survival ratio.